Equity and child-survival strategies - EK Mulholland; L Smith; I Carneiro; H Becher; D Lehmann (The World Health Organization, 2008)
Recent advances in child survival have often been at the expense of increasing inequity. Successive interventions are applied to the same population sectors, while the same children in other sectors consistently miss out, leading to a trend towards increasing inequity in child survival. This is particularly important in the case of pneumonia, the leading cause of child death, which is closely linked to poverty and malnutrition, and for which effective community-based case management is more difficult to achieve than for other causes of child death. The key strategies for the prevention of childhood pneumonia are case management, mainly through Integrated Management of Childhood Illness (IMCI), and immunization, particularly the newer vaccines against Haemophilus influenzae type b (Hib) and pneumococcus. There is a tendency to introduce both interventions into communities that already have access to basic health care and preventive services, thereby increasing the relative disadvantage experienced by those children without such access. Both strategies can be implemented in such a way as to decrease rather than increase inequity. It is important to monitor equity when introducing child-survival interventions. Economic poverty, as measured by analyses based on wealth quintiles, is an important determinant of inequity in health outcomes but in some settings other factors may be of greater importance. Geography and ethnicity can both lead to failed access to health care, and therefore inequity in child survival. Poorly functioning health facilities are also of major importance. Countries need to be aware of the main determinants of inequity in their communities so that measures can be taken to ensure that IMCI, new vaccine implementation and other child-survival strategies are introduced in an equitable manner.